Identification of Plasmatic MicroRNA-206 as New Predictor of Early Recurrence of Atrial Fibrillation After Catheter Ablation Using Next-generation Sequencing - Šustr, Filip; Macháčková, Táňa; Pešl, Martin; Svačinova, Jana; Trachtová, Karolína; Stárek, Zdeněk; Kianička, Bohuslav; Slabý, Ondřej; Novák, Jan (Molecular diagnosis & therapy, 2024)
BACKGROUND: Catheter ablation (CA) of atrial fibrillation (AF) is indicated in patients with recurrent and symptomatic AF episodes. Despite the strict inclusion/exclusion criteria, AF recurrence after CA remains high. Identification of a novel biomarker that would predict AF recurrence would help to stratify the patients. The aim of the study was to seek novel biomarkers among the plasmatic microRNAs (miRNAs, miRs). METHODS: A prospective monocentric study was conducted. A total of 49 consecutive AF patients indicated for CA were included. Blood sampling was performed prior to CA. RNA was isolated from plasma using commercial kits. In the exploration phase, small RNA sequencing was performed in ten AF patients (five with and five without AF recurrence) using Illumina instrument. In the validation phase, levels of selected miRNAs were determined using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in all participants. RESULTS: Altogether, 22 miRNAs were identified as altered between the groups by next-generation sequencing (using the DESeq2 algorithm). Using qRT-PCR, levels of the five most altered miRNAs (miR-190b/206/326/505-5p/1296-5p) were verified in the whole cohort. Plasma levels of hsa-miR-206 were significantly higher in patients with early (within 6 months) AF recurrence and showed an increase of risk recurrence,2.65 times by every increase in its level by 1 unit in the binary logistic regression. CONCLUSION: We have identified a set of 22 plasmatic miRNAs that differ between the patients with and without AF recurrence after CA and confirmed hsa-miR-206 as a novel miRNA associated with early AF recurrence. Results shall be verified in a larger independent cohort.
Keywords: Recurrence; Female; biologické markery; Atrial Fibrillation; Biomarkers; ženské pohlaví; High-Throughput Nucleotide Sequencing; Catheter Ablation; lidé; recidiva; katetrizační ablace; prognóza; prospektivní studie; Male; Aged; Prospective Studies; vysoce účinné nukleotidové sekvenování; mikro RNA; Prognosis; MicroRNAs; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans